Developing Concept Approach Based Textbooks of Social Sciences Course for Madrasah Ibtidaiyah Teacher Education - M Irfan Islamy (Al Ibtida: Jurnal Pendidikan Guru MI, 2019)
AbstractThe development of the Madrasah Ibtidaiyah/Elementary School curriculum has changed several times, from the KBK Curriculum to KTSP Curriculum, then to the 2013 Curriculum. However, the limited textbooks that are in accordance with the curriculum changes are obstacles to learning achievement, especially in Social Sciences course for elementary school teacher education. This study aims to develop a social science course textbook for Madrasah Ibtidaiyah/elementary school teacher education with a 2013 curriculum-based concept approach that is appropriate for students taking Social Sciences Madrasah Ibtidaiyah/elementary school teacher education courses. This research uses a 4-D model with stages of Define, Design, Develop, and restrictions on Desseminate. The results showed that the development of concept approach based social science course textbooks for Madrasah Ibtidaiyah/elementary school got a very decent category with a score of 81% from material experts, a decent category with a score of 80% from linguists, and a very decent category with a score of 87% from design experts. So it can be concluded that the textbooks for Social Sciences of Madrasah Ibtidaiyah/elementary school teacher education using the 2013 curriculum-based concept are categorized as feasible.Keywords: concept approach, social studies education, development of textbooks.                                                                                                                 AbstrakPerkembangan kurikulum Madrasah Ibtidaiyah/Sekolah Dasar telah beberapa kali mengalami perubahan, dari Kurikulum Berbasis Kompetensi ke Kurikulum Tingkat Satuan Pendidikan, kemudian ke Kurikulum 2013. Akan tetapi, terbatasnya buku ajar yang sesuai dengan perubahan kurikulum tersebut menjadi kendala terhadap tercapainya pembelajaran, khususnya pada mata kuliah Pendidikan IPS MI/SD. Penelitian ini bertujuan untuk mengembangkan buku ajar mata kuliah Pendidikan IPS MI/SD dengan pendekatan konsep berbasis kurikulum 2013 yang layak untuk mahasiswa yang mengambil mata kuliah Pendidikan IPS MI/SD. Penelitian pengembangan ini menggunakan model 4-D dengan tahapan Define, Design, Develop, dan pembatasan pada Desseminate. Hasil penelitian menunjukkan bahwa pengembangan buku ajar Pendidikan IPS MI/SD mendapatkan kategori sangat layak dengan skor 81% dari ahli materi, kategori layak dengan skor 80% dari ahli bahasa, dan kategori sangat layak dengan skor 87% dari ahli desain. Sehingga dapat disimpulkan bahwa buku ajar mata kuliah Pendidikan IPS MI/SD menggunakan konsep berbasis kurikulum 2013 dikategorikan layak.Kata Kunci: pendekatan konsep, pendidikan IPS, pengembangan buku ajar.